Relevansi Ajaran Tasawuf terhadap Pembinaan Moral Generasi Milenial - Ainur Rofiq (LP3M IAI Al Urwatul Wutsqo Jombang, 2024)
The moral crisis among millennials has become a major challenge in the digital era, characterized by technological advancement, consumerism, and an instant-gratification culture. This study aims to analyze the relevance of Sufism teachings to the moral development of the millennial generation in the context of modern life. Using a qualitative library-based approach, this research explores classical works such as Ihya ‘Ulum al-Din, al-Risalah al-Qusyairiyyah, and al-Hikam, complemented by contemporary academic sources. The findings reveal that Sufism provides substantial contributions to the ethical, spiritual, and social awareness of millennials through the internalization of tazkiyatun nafs, muhasabah, zuhud, sabr, and ikhlas. These values guide individuals to cultivate self-control, sincerity, simplicity, and moral responsibility amid the dominance of social media and materialism. Conceptually, Sufism offers a spirituality-based moral education model emphasizing inner transformation as the foundation of social ethics. The study recommends integrating Sufi values into Islamic education to shape morally resilient, religious, and ethically conscious young generations